What is an ELA text set? Surveying and integrating cognitive, critical and disciplinary lenses. Issue 1 (1st February 2022) - Reynolds, Dan
Abstract : Purpose: Researchers and teachers have noted the power of students reading text sets or multiple texts on the same topic, and numerous articles have been published with examples of and frameworks for text set construction. This study aims to traces the theoretical assumptions of these frameworks and explores their distinct implications and tensions for understanding disciplinary literacy in English language arts (ELA). Design/methodology/approach: The author draws on three frameworks, using a focal article for each: cognitive (Lupo et al., 2018), critical (Lechtenberg, 2018) and disciplinary (Levine et al., 2018), and connect those articles to other research studies in that tradition. Separately, the author describes each of the three text set frameworks' design principles. Then, across frameworks, the author analyze the disciplinary assumptions around each framework's centering texts, epistemological goals and trajectories. Findings: The centering text, goals and trajectories of each framework reflect its underlying epistemological lens. All frameworks include a text that serves as its epistemological center and the cognitive and disciplinary frameworks, both rely on progressions of complexity (knowledge/linguistic and literary, respectively). The author traces additional alignments and tensions between the frameworks and offer suggestions for possible hybridities in reading modality and reading volume. Originality/value: Many articles have been written about models of text set construction, but few have compared the assumptions behind those models. Examining these assumptions may help English teachers and curriculum designers select texts and build curriculum that leverages the strengths of each model and informs researchers' understanding of disciplinary literacy in ELA.